(untitled) (American Journal of Technology and Applied Sciences, 2025)
Digitalization in dentistry opens up wide opportunities for improving the quality and effectiveness of the treatment process. This study is devoted to the study of the implementation of innovative digital technologies in dental practice and their impact on the manufacture of prosthetic structures.